SOSIALISASI DAN PELATIHAN PEMBUATAN NUGGET IKAN SEBAGAI SALAH SATU CARA EFEKTIF DALAM PENGENTASAN STUNTING PADA ANAK USIA DINI SERTA IBU HAMIL - Dian Iriani; Siti A’isah; Fitri Iska Yuliana; Ahmad Ramadhan Mubarak; Dila Azzahra Salsabila; Retna Monika; Anisatun Nabilah; Wahyu Sukma Putra Yandri; Nadia Atika; Efendi Juprias; Yovianda Yovianda (Universitas Pahlawan Tuanku Tambusai, 2022)
Benteng Hulu Village is a village located in Mempura District, Siak Regency, Riau Province. This village has 14 neighborhood units and 3 hamlets which are not too far away. As a fairly large village, of course, there are always problems that occur, as we hear the most about Stunting. The problem of Stunting is influenced by several factors such as lack of understanding of health in early childhood and lack of initiative in developing nutrition for pregnant women. Therefore, we Riau University students took the initiative in the context of community service to hold outreach about alleviating Stunting and provide innovative nutritious food by making fish nuggets as a way to minimize Stunting cases. The method used is a field study method where the author is directly involved and goes into the field in activities in Benteng Hulu Village. This community service is carried out within 1 month. From the activities carried out, concluded two things, namely: 1). The community needs education about understanding about Stunting 2). The community needs to be given a solution for how to minimize the occurrence of Stunting in an innovative way in improving nutrition. Keywords: Community Service, Stunting, Socialization, Fish Nuggets